A First-Principles Study on Defects in Zirconium Monoxide - Hanyu Shi; Zhixiao Liu; Dong Wang; Tianguo Wei; Yi Zhao (Metals)
Zirconium monoxide (ZrO) plays a key role in the water-side corrosion resistance of Zr alloys as cladding materials in nuclear reactors. This study investigates the behavior of intrinsic defects in ZrO through first-principles calculations, and the influence of main alloying elements (Cr, Fe, Nb and Sn) is also evaluated. We focus on the formation and migration properties of vacancies and interstitials. The results show that the formation energy of oxygen vacancy is 5.31 eV. The formation energy of interstitial Oi-tet in ZrO is −4.04 eV, indicating that Oi-tet can be formed spontaneously. Another interstitial oxygen Oi-mid with a formation energy of 0.03 eV can also be found in large quantities in ZrO. As for the migration properties, oxygen vacancy in ZrO without doping tends to diffuse along Path 2, and the diffusion barrier is 2.96 eV. Cr and Fe reduce the migration barriers of oxygen vacancies, while Nb and Sn increase them. In contrast, alloying elements generally hinder the formation of oxygen interstitials and increase their migration barriers, particularly in the case of Cr and Fe. The migration barrier of interstitial oxygen diffusion along Path a in pure ZrO is 2.91 eV. However, the migration barriers of interstitial oxygen in ZrO with Cr or Fe doping could increase to more than 4 eV. These findings provide critical insights into the role of alloying elements in modifying defect dynamics, offering a theoretical basis for improving the corrosion resistance and performance of zirconium alloys in practical applications.